2022
DOI: 10.47203/ijch.2022.v34i03.002
|View full text |Cite
|
Sign up to set email alerts
|

Implementation challenges of Pradhan Mantri Jan Arogya Yojana: A Cross- Sectional study in Meerut, Uttar Pradesh

Abstract: Background: Ayushman Bharat – Pradhan Mantri Jan Arogya Yojana has been launched to provide financial protection expenditure to nearly 500 million vulnerable Indians. For expanding the coverage under the scheme, it is necessary to understand the perspective of health care service providers involved in the scheme. Aim & Objective: To find out the bottlenecks in implementation of PMJAY scheme using empanelled hospitals’ perspective Settings and Design: Cross sectional study Methods and Material: 8 Public and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, a cross-sectional study in Uttar Pradesh (UP) indicated that a majority of hospitals (93.5%) were satisfied with the empanelment process. 70 Satisfaction concerning packages was low (35.5%). Overall, PMJAY was perceived to be inferior to private insurance by 77.4% of providers due to poor grievance redressal mechanisms, claim processing delays, and lower health packages rate which has resulted in disinterest in implementing scheme and sometime suspension of implemented scheme.…”
Section: Pradhan Mantri Jan Arogya Yojanamentioning
confidence: 97%
See 1 more Smart Citation
“…However, a cross-sectional study in Uttar Pradesh (UP) indicated that a majority of hospitals (93.5%) were satisfied with the empanelment process. 70 Satisfaction concerning packages was low (35.5%). Overall, PMJAY was perceived to be inferior to private insurance by 77.4% of providers due to poor grievance redressal mechanisms, claim processing delays, and lower health packages rate which has resulted in disinterest in implementing scheme and sometime suspension of implemented scheme.…”
Section: Pradhan Mantri Jan Arogya Yojanamentioning
confidence: 97%
“…Overall, PMJAY was perceived to be inferior to private insurance by 77.4% of providers due to poor grievance redressal mechanisms, claim processing delays, and lower health packages rate which has resulted in disinterest in implementing scheme and sometime suspension of implemented scheme. 70 , 71 Insurance agencies also concurred that premium rates quoted are low (about ten times lower than the market prices). 71…”
Section: Pradhan Mantri Jan Arogya Yojanamentioning
confidence: 99%